God So Enters into Relationships That . . . : A Biblical View - Fretheim, Terence E. (Word & world books., 2020)
Biblical theologian Terence E. Fretheim weaves key insights from Scripture with theological reflections on the nature and activity of God, God's relationship to the world, and the natural order. Relational language and images fill the various forms of communication that ministry leaders must use to speak about God and God's presence and activity in the world. Fretheim shows the importance of using this kind of language to speak to the realities of life and faith. Each chapter of the book will explore a unique aspect of God's relationship with humanity and the world, including God's faithfulness, concern for our entire selves, promise to be present in both good and bad times, willingness to listen, sharing of power, and desire to allow an open future for all. Filled with authentic reflections and helpful insights, this is a must-read for all want to know and experience more about the nature of God.